Facing homelessness Finding - de Beer, Stephan (AOSIS, 2021)
In facing homelessness we face the other, and in facing the other, we face ourselves. This book contributes to an emerging body of knowledge on street homelessness in the South African context. It is meant for researchers and scholars who are committed to finding solutions for street homelessness. It offers conceptual frameworks and practical guidelines for a liberative and transformative response to homelessness. It brings together authors from a wide range of disciplines, fusing the rigour of researchers, the vision of activists and the lived experience of practitioners. In this volume, the causes of street homelessness in South Africa today, and its different faces, are traced. It critiques singular solutions, and interrogates the political, institutional and moral failures that contribute to the systemic exclusion of homeless persons and other vulnerable populations from society. It proposes rights-based interventions as part of a radical re-imagination of how street homelessness can be ended, one person and one neighbourhood at a time. The analysis by the authors steer in the direction of new ways of doing and being that could demonstrate concrete, viable and sustainable alternatives to the exclusionary realities faced by homeless persons. It argues for solution-based approaches, aimed at radical forms of social inclusion and achieved through broad-based and creative collaborations by all spheres of society. In the face and presence of street homelessness - as one expression of urban vulnerability and deep socio-economic inequality - society is confronted with a clear political, institutional, moral and personal obligation. This volume calls for a reclamation of community in its most inclusionary, life-affirming and interdependent sense, asserting that we truly are well because of others, and we are unwell if others are. It is a call to reclaim our common humanity in the context of inclusive communities where all are equally welcome and bestowed with dignity and honour.